Theory Of Planned Behavior Terhadap Kinerja Mahasiswa dengan Mind Mapping sebagai Mediasi - Tri Danarti; Sentot Imam Wahjono; Siti Salbiyah (UMSurabaya Publishing, 2021)
This study aims to determine the positive and significant effect of Theory of Planned Behavior on Student Performance directly and the effect of Theory of Planned Behavior on Student Performance through Mind Mapping Mediation. This study uses a descriptive quantitative approach, with a population of two hundred and thirty-six students from Bureau data. Academic, University of Muhammadiyah Surabaya, Faculty of Economics and Business who have passed the introductory business course with Mind Mapping mediation and the samples taken are one hundred forty-two students. The results of this study are that there is a positive and significant influence of Theory of Planned Behavior on the performance of students of the Faculty of Economics and Business, Muhammaiyah University Surabaya through Mind Mapping mediation. Keywords : Theory of Planned Behavior; Mind Mapping; Introduction to BusinessABSTRAK (Bahasa Indonesia)Penelitian ini bertujuan untuk mengetahui pengaruh positif dan signifikan dari Theory of Planned Behavior terhadap Kinerja mahasiswa secara langsung dan pengaruh Theory of Planned Behavior terhadap Kinerja mahasiswa melalui Mediasi Mind Mapping. Penelitian ini menggunakan pendekatan kuantitatif deskriptif, dengan populasi dua ratus tiga puluh enam mahasiswa dari data Biro Akademisi Universitas Muhammadiyah Surabaya Fakultas Ekonomi dan Bisnis yang telah lulus mata kuliah pengantar bisnis dengan mediasi Mind Mapping dan sampel yang diambil sebanyak seratus empat puluh dua mahasiswa. Hasil penelitian ini adalah terdapat pengaruh yang positif dan signifikan antara Theory of Planned Behavior terhadap Kinerja Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surabaya melalui mediasi Mind Mapping. Kata Kunci : Theory of Planned Behavior; Mind Mapping; Pengantar Bisnis